10-year Portuguese football strategic plan: sustainable growth- street football - Silva, Afonso Pedro Martins Lima da Costa (2022)
This thesis project complements the strategic plan about the vision of Portuguese football in 2030 conducted in partnership with FPF and Deloitte, which includes the pillars: women’s football, fan engagement, academic football, broadcasting rights, and internationalization. Considering street football’s history and its recent decline, the study intends to identify the added value of this strand of the sport, characterize its particularities, and verify its importance to players’ development. In addition, it focuses on understanding how the change in children’s habits may affect the retention rate of participants and how the diminishing of street football will impact the future game’s quality.